Posttraumatic Growth After Birth Trauma: "I Was Broken, Now I Am Unbreakable". Issue 5 (September 2016) - Beck, Cheryl Tatano; Watson, Sue
Abstract: Purpose: The aim of this study was to investigate women's experiences of posttraumatic growth following traumatic childbirth. Study Design and Methods: A descriptive phenomenological study was conducted using Colaizzi's data analysis method. The Internet sample of 15 mothers was recruited from the Trauma and Birth Stress Web site. Women were asked to describe in as much detail as they could remember, their experiences of any positive changes in their beliefs or life as a result of their traumatic childbirth. Results: Using Calhoun and Tedeschi's metaphor of an earthquake to help explain posttraumatic growth, the seismic waves of birth trauma had enough power to lead to four themes of posttraumatic growth revealed in this phenomenological study: (1) Opening oneself up to a new present, (2) Achieving a new level of relationship nakedness, (3) Fortifying spiritual-mindedness, and (4) Forging new paths. Clinical Implications: Mothers' experiences of their personal growth after birth trauma can help inform future research that can promote posttraumatic growth in mothers. Clinicians can share results of this study with their patients to provide some hope to mothers struggling with the aftermath of a traumatic birth that some women have reported positive growth. Healthcare providers need to respect trauma survivors' struggles while at the same time permitting mothers to explore possibilities for growth. Clinicians must not, however, create the false expectation that posttraumatic growth will happen in most trauma survivors. Abstract : This study was conducted by one of the leading experts in the field, Dr. Cheryl Beck, along with her colleague Sue Watson, and offers a unique view of how some mothers have reported positive growth after a traumatic birth experience. Findings can help nurses better understand mothers' experiences and inform future nursing research.